Isolation and identification of entomopathogenic fungus from Eastern Ghats of South Indian forest soil and their efficacy as biopesticide for mosquito control. (June 2020) - Vivekanandhan, P.; Bedini, S.; Shivakumar, M.S.
Abstract: The repeated usage of chemical insecticides, responsible for insecticide resistance in mosquitoes and environmental toxicity. Currently effective and environmental-safe control strategies are needed for the control disease-vector mosquitoes. Entomopathogens can be an effective alternative to chemical insecticide. Herein we isolated and tested 46 soil-borne entomopathogenic fungi belonging to six genera, namely Beauveria sp., Metarhizium sp., Fusarium sp., Aspergillus sp., Trichoderma sp., and Verticillium sp., fungi conidia were tested on Aedes aegypti, Anopheles stephensi and Culex quinquefasciatus larvae. Bioassays results show that M. anisopliae fungal isolate causes a 100%, 98.6% and 92% mortality within six days, on Aedes aegypti, Anopheles stephensi and Culex quinquefasciatus, respectively. M. anisopliae treated three mosquito larvae have lower lifetime with LT50 values in A. stephensi, 2.931 days; A. aegypti, 2.676 days and C. quinquefasciatus, 3.254 days. 18 s rDNA sequence analysis confirmed that the isolated fungus are belonging to the genus of M. anisopliae -VKKH3, B. bassiana -VKBb03, and V. lecanii- VKPH1. Our results clearly show that M. anisopliae has good potential, as a low-cost, environmentally safe tool for the control of A. aegypti, A. stephensi, and C. quinquefasciatus mosquitoes. Highlights: Soil samples collected from Eastern Ghats of South Indian forest . Entomopathogenic fungi isolated from soil using Galleria Bait Method. Entomopathogens M. anisopliae -VKKH3, B. bassiana -VKBb03 and V. lecanii- VKPH1 identified using 18 s r DNA sequence M. anisopliae -VKKH3 shows highest virulence against mosquitoes.